KONDISI FISIOLOGIS MAHASISWA RANTAU DARI JAWA DI TAHUN PERTAMA KULIAH DI FAKULTAS MIPA UNIVERSITAS UDAYANA - Ayesha Audreyhan; Ida Bagus Made Suaskara; I Ketut Muksin (Program Studi Biologi Universitas Udayana, 2025)
Physiological conditions are normal body functions in humans that undergo adaptation and refer to physical changes, especially in probandus who are migrating in a new environment. Students who migrate often experience various physiological condition challenges, such as changes in the amount of hemoglobin levels, blood pressure, and body weight. This study aims to determine the physiological conditions between male and female students who migrate from Java in the first year of study at the Faculty of Mathematics and Natural Sciences, Udayana University. The method of data collection was carried out in a qualitative way, namely interviews and quantitative ways, namely hemoglobin level tests, blood pressure tests, and weight measurements taken through male and female probandus. The results showed that hemoglobin levels in female probandus in the first year of college increased significantly compared to male probandus, which showed that female probandus were more able to adapt to the new environment. Blood pressure checks during the fasting month did not show significant changes in both female and male probandus, due to changes in diet during fasting that affect metabolism. Body weight before and after migrating also did not experience significant changes, which indicates changes in diet, physical activity and the adaptation of body metabolism as well as balanced calorie intake are factors that influence body weight. Keywords: psychological condition, overseas student, udayana university.